Beliefs about causes of psychotic disorders and subsequent help-seeking behaviour in caregivers presenting at the department of psychiatry, civil hospital, Karachi - Muhammad Ilyas jat; Kumar, Ravi; Khan, Bilal Ahmed; Bin Nazir, Maaz; Javed, Maliha; Farooq, Aisha (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the beliefs about causes of psychotic disorders and subsequent help-seeking behaviour in caregivers. Method: The descriptive cross-sectional study was conducted at the Department of Psychiatry, Civil Hospital, Karachi, from September 2020 to February 2021, and comprised caregivers of patients with psychotic disorders. Data was collected using a questionnaire that was filled up by caregivers mentioning their beliefs about the cause of the disorder and subsequent help-seeking behaviour. Data was analysed using SPSS 22. Results: Of the 162 participants, 69(42.6%) were male and 93(52.4%) were female. The overall mean age was 39.9+12.9 years. The majority 157(96.9%) subjects were Muslims. In terms of beliefs, anxious personality 62(38.3%), evil eye 62(38.3%) and God’s will 56(34.6%) were the major choices picked. With respect to help-seeking behaviour, the choices most picked were taking the patient to a psychiatrist 129(79.6%), praying 108(66.6%) and taking the patient to a family physician 103(63.6%). Conclusion: There was found to be sufficient awareness among the caregivers, but help-seeking behaviour needed to improve considerably. Key Words: Beliefs, Causes, Help-seeking, Psychotic.